Assessment of the prescription of red blood cell concentrates in the pediatric age group - Pina Faria, Joao Carlos (2018)
Objective: To verify the adequacy of red blood cell (RBC) prescription to pediatric patients in different sectors of a pediatric hospital. Method: A retrospective study was conducted including 837/990 RBC transfusion requisition forms for children and adolescents (0 to 13 years old) filed in between January 2007 and April 2015 by the pediatricians of the emergency room (ER), infirmary ward and intensive care unit (pICU). Transfusion requisition forms belonging to patients with chronic anemia or acute hemorrhage, as well as incompletes requisition forms, were excluded. Results: Trigger, prescribed volume and subtype of RBC concentrates were adequate in 532 (65.3%), 460 (58.8%) and 805 (96.2%) of the transfusions, respectively. When the clinical picture was considered, prescription adequacy was higher compared to the use of the hemoglobin level alone (70.9% vs. 41%). The pICU had the highest correct trigger percentage (343 [71.6%]